Interactive Multimedia Technology for Geometry Learning: Integrating Ethnomathematics and Mobile Learning - Osniman Paulina Maure; Konradus Silvester Jenahut; Gabariela Purnama Ningsi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The study aims to develop and evaluate mobile learning media based on ethnomathematics, using Articulate Storyline integrated with a problem-based learning model, to support interactive, contextual and meaningful geometry learning for junior secondary school students. Methodology: A research and development approach was employed using the ADDIE model. Participants consisted of 38 junior secondary school students involved in small- and large-scale trials. Data were collected through expert validation sheets, questionnaires and implementation evaluations. These were analysed using descriptive statistics, supported by percentage categories and triangulation from expert, teacher and student responses. Main Findings: The developed mobile learning media were categorised as highly valid by experts in the field of media, subject matter and language. Implementation results indicate that the media is practical and well accepted by users. The findings also demonstrate its potential to support students' conceptual understanding of geometry and to enhance their interest in learning it through interactive multimedia features and culturally contextualised content from East Nusa Tenggara. Novelty/Originality of this study: This study contributes to the field by integrating ethnomathematics, mobile learning and problem-based learning within a single instructional design using Articulate Storyline. Unlike previous studies that examined these approaches separately, this study emphasises the contextualisation of geometry concepts through local cultural elements, providing a culturally responsive, technology-enhanced learning approach.